Prosthetic leg design, force production, and curve sprint performance: a pilot study - Alcantara, R. S. (ISBS Proceedings Archive (Michigan), 2020)
We compared the use of a running specific prosthesis (RSP) with a solid or "split-toe" design by athletes with a leg amputation on sprinting speed and stance-average centripetal ground reaction force (GRF) along a flat 400 m track curve, 200 m track curve, and straightaway. Three athletes with a right transtibial amputation performed maximal effort sprints along the curves (clockwise and counterclockwise) and straightaway of an indoor track using a traditional, solid RSP and an RSP with a split-toe design while we measured 3D GRFs and kinematics. Sprinting speed was significantly faster (p = 0.003) when using the split-toe RSP across curve conditions and directions compared to the solid RSP. However, there was no significant effect of RSP design on stance-average centripetal force (p = 0.180). Sprint speed was similar between RSP designs on the straightaway (p = 0.705).